2015
DOI: 10.3390/molecules201019030
|View full text |Cite
|
Sign up to set email alerts
|

miRNA Stability in Frozen Plasma Samples

Abstract: MicroRNAs (miRNAs) represent a family of small non-coding ribonucleic acids that post-transcriptionally inhibits the expression of their target messenger RNAs (mRNAs), thereby acting as general gene repressors. In this study we examined the relative quantity and stability of miRNA subjected to a long period of freezing; we compared the stability of eight miRNAs in the plasma of five human healthy controls before freezing and after six and 12 months of storage at −80 °C. In addition, we examined the plasma froz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 25 publications
2
71
1
2
Order By: Relevance
“…Because of plasma miRNAs' high stability under handling and storage conditions [17], they have the potential to become novel diagnostic biomarkers for cancer [18,19], respiratory diseases [20], and other conditions. Nonsyndromic cleft lip is one type of oral clefting without cleft palate or other developmental syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Because of plasma miRNAs' high stability under handling and storage conditions [17], they have the potential to become novel diagnostic biomarkers for cancer [18,19], respiratory diseases [20], and other conditions. Nonsyndromic cleft lip is one type of oral clefting without cleft palate or other developmental syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…One benefit of extracellular miRNAs as CVD biomarkers is that they can be sampled non-invasively and are present in all biological fluids (Boon & Vickers, 2013). miRNA biomarker studies also benefit from the high stability and relatively long half-life of miRNAs in samples, the required low input for detection, the high specificity of currently available probes, and the increasing available detection strategies and technologies (Balzano, et al, 2015; Creemers, Tijsen, & Pinto, 2012). Aside from diagnostic potential and monitoring response to drug treatments, miRNA-based therapy is a rapidly emerging market that is proving to be very lucrative to the pharmaceutical industry -- expected to reach 1 billion in 2019 (www.bccresearch.com).…”
Section: Current Development Of Mirna Therapeutics That May Impactmentioning
confidence: 99%
“…Previous reports have shown that miRNAs participate in some cell signaling processes, including apoptosis, cell proliferation, and epithelial-to-mesenchymal transition [19, 20]. Quantification of miRNA expression can be performed even using relatively degraded samples, such as FFPE samples, in a PCR-based test (real-time PCR) [14, 21-23]. In this study, we used FFPE samples as well as snap-frozen samples (different quality of RNA) and examined the expression of several candidate miRNAs.…”
Section: Discussionmentioning
confidence: 99%